N06 Assessing stakeholder identified barriers and enablers to Ultrasound implementation for assessment of Crohn's Disease in the UK: A qualitative interview study. (21st January 2022) - Radford, S; Leighton, P; Coad, J; Moran, G
Abstract: Background: Data from the METRIC trial (PMID:29914843) has shown that small bowel ultrasound (US) has very good diagnostic accuracy for disease extent, presence and activity in Crohn's Disease, is well tolerated by patients and is cheaper when compared to MRI. A recent survey (unpublished) undertaken by the authors via the British Society of Gastroenterology indicated that there is enthusiasm for the use of US in IBD care in the UK. However, uptake of US in the UK is limited, however it is unclear why this is the case. Methods: A qualitative semi-structured interview study, utilising template analysis using the Normalisation Process Theory (NPT) codebook, was undertaken. NPT was used to guide the analysis framing the findings in relation to the implementation processes related to integrating US into daily IBD care. Interviews were undertaken utilising virtual meeting software. Results: Fourteen participants were enrolled in the interview study (table #). Participants were enrolled between 02/06/2021-and 06/09/2021, with interviews taking place during the same time period. Enrolled were three patients living with CD (21.4%), two IBD Nurse specialists (14.3%), two IBD Nurse consultants (14.3%), one surgical IBD nurse specialist (7.1%), two consultant gastroenterologists (14.3%), two consultant radiologists (14.3%) and two gastroenterology service managers (14.3%). Participants reported that perceived barriers included reliance on MRI and established care pathways, reluctance to change, lack of trust in US in relation to perceived lack of precision when compared to MRI and the initial financial and time outlay in establishing a US service (buying equipment and training staff). Participants were enthusiastic for the uptake of US and discussed enablers to US uptake being the benefits to patients in terms of reduction in waiting times and earlier diagnosis and treatment allocation (leading to improved clinical outcomes), reduced hospital appointments, reduced costs to the NHS, patients having better understanding of their health and improvements in the therapeutic relationships between patients and healthcare professionals. Conclusion: There is an enthusiasm to establish and utilise US in IBD care in the UK, however there are perceived barriers in achieving this. There is scant literature to effectively assess these reported barriers and enablers. Therefore there is further research required in the areas of the impact of the use of US on the confidence of clinical decision making of healthcare professionals and the relative cost effectiveness when compared to MRI use for the assessment of IBD in the UK.